Modelling hemodynamics regulation in rats and dogs to facilitate drugs safety risk assessment - Morris, Christopher J.; Rolf, Michael G.; Starnes, Linda; Villar, Inmaculada C.; Pointon, Amy; Kimko, Holly; Di Veroli, Giovanni Y. (Frontiers in Pharmacology, 2024)
Pharmaceutical companies routinely screen compounds for hemodynamics related safety risk. In vitro secondary pharmacology is initially used to prioritize compounds while in vivo studies are later used to quantify and translate risk to humans. This strategy has shown limitations but could be improved via the incorporation of molecular findings in the animal-based toxicological risk assessment. The aim of this study is to develop a mathematical model for rat and dog species that can integrate secondary pharmacology modulation and therefore facilitate the overall pre-clinical safety translation assessment. Following an extensive literature review, we built two separate models recapitulating known regulation processes in dogs and rats. We describe the resulting models and show that they can reproduce a variety of interventions in both species. We also show that the models can incorporate the mechanisms of action of a pre-defined list of 50 pharmacological mechanisms whose modulation predict results consistent with known pharmacology. In conclusion, a mechanistic model of hemodynamics regulations in rat and dog species has been developed to support mechanism-based safety translation in drug discovery and development.